Machine learning and AI beyond the basics advanced questions and answers on machine learning and AI - Raschka, Sebastian (No Starch Press, 2024)
"An advanced exploration of machine learning and AI, with each chapter asking and answering a question from the field. Divided into five sections: deep learning and neural networks; computer vision; natural language processing; production and deployment; and predictive performance and model evaluation"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Artificial intelligence; Machine learning; Computer vision; Neural networks (Computer science); Natural language processing (Computer science); Intelligence artificielle; Apprentissage automatique; Vision par ordinateur; Réseaux neuronaux (Informatique); Traitement automatique des langues naturelles; artificial intelligence